Uji Toksisitas Akut Kulit Kentang (Solanum tuberosum L.) Terhadap Larva Artemia salina Leach Dengan Metode BSLT (Brine Shrimp Lethality Test) - Baterun Kunsah (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2019)
Tanggal Submit:28 Januari 2019 Tanggal Review:30 April 2019 Tanggal Publish Online:17 Mei 2019 Potatoes are one of the vegetables that contain substances that are important for the formation of body tissues, such as protein and fat. Potatoes also form red blood cells or hemoglobin (Ca, P and Fe). In Indonesia tend to process potatoes using only meat. The skin is removed, even though the nutritional content of the skin is five times greater than the meat. Potato peels that supply querestin, antioxidants and flavonoids that act as free radical acceptors. (Free radicals are reactive molecules that cause damage to the body that can lead to diseases such as heart disease and cancer) in the skin of potatoes found also effective antioxidants, chlorogenic acid. Potato skin is also proven to increase hemoglobin levels (Khomsan, A, 2009). However, that does not mean potato skin does not have adverse side effects, if the use is not appropriate. In order to use it optimally, you need to know enough information about the advantages and disadvantages and the possibility of abuse. However, the level of toxicity from potato skin is still unknown. Brine Shrimp Lethality Test (BSLT) is one of the oxicity test methods that is widely used in tracing bioactive compounds that are toxic from natural materials. This research is an experimental research with post test-only control group design approach. Treatment with giving potato skin juice to Artemia salina Leach larvae with the aim to determine the potential of plant biological activity based on the toxicity of secondary metabolites contained in it, and at the same time as the initial screening test of anticancer activity of chemical compounds in potato skin juice. The results showed the LC50 value was at a concentration of 0.5% to 1% and based on the results of SPSS 21 analysis with probit analysis obtained LC50 price data of 0.746 gr / ml (7460 μgr / ml), based on the results of research and data analysis it can be concluded that potato skin has an LC50 value at a concentration of 0.746 gr / ml (7460 µgr / ml). With an LC50 price of more than 1000 µg / ml according to the BST method the potato skin does not have the potential for toxicity so the skin of the potato has the potential as an alternative to increasing hemoglobin levels.Keywords: potato skin, toxicity, BSlT